Kajian Kinerja Keuangan dengan Metode Rasio Profitabilitas pada PT Akasha Wira International Tbk Periode 2022-2024 - Adela Nur Asyifa; Sonia Ayu Febrianty; Abdillah Abdillah (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to evaluate the financial performance of PT Akasha Wira International Tbk during the period 2022 to 2024 using profitability ratio analysis. The ratios analyzed include Return on Assets (ROA), Return on Equity (ROE), Gross Profit Margin (GPM), Operating Profit Margin (OPM), and Net Profit Margin (NPM). The data used is sourced from official financial statements published through the Indonesia Stock Exchange website. Based on the results of the analysis, the company's financial performance is generally relatively good and shows stability over the past three years. This is reflected in the consistency of the profitability ratio which is at a favorable level, indicating the effectiveness of the company in managing assets, its own capital, production costs, and operational activities. Further analysis shows that the Return on Assets and Return on Equity show a stable trend with a slight increase, which indicates efficiency in asset utilization and capital management. Gross Profit Margin and Operating Profit Margin also show positive trends, indicating efficiency in managing production costs and operational activities. Net Profit Margin, although slightly volatile, remains within a range that reflects good profitability. In addition, the results of this evaluation also indicate that the company has the ability to adapt to market changes and dynamic economic conditions. The ability to maintain profit margins in the midst of economic fluctuations shows the resilience of the business model and operational strategy applied. These findings provide an idea that PT Akasha Wira International Tbk has been able to maintain a healthy performance despite being in a competitive business environment. Thus, the results of this evaluation can be used as a basis for strategic considerations by management in preparing long-term financial plans and decision-making, as well as a reference for investors in assessing the company's prospects.